Hepatitis E seroprevalence in recipients of renal transplants or haemodialysis in southwest England: A case–control study1. Issue 2 (20th November 2012) - Harrison, Alex; Scobie, Linda; Crossan, Claire; Parry, Rob; Johnston, Paul; Stratton, Jon; Dickinson, Steve; Ellis, Vic; Hunter, Jeremy G.; Prescott, Oliver R.; Madden, Richie; Lin, Nan X.; et al.
Abstract Locally acquired HEV infection is increasingly recognized in developed countries. Anti‐HEV IgG seroprevalence has been shown to be high in haemodialysis patients in a number of previous studies, employing assays of uncertain sensitivity. The aim of this study was to investigate anti‐HEV IgG seroprevalence in recipients of haemodialysis and renal transplants compared to a control group using a validated, highly sensitive assay. Eighty‐eight patients with functioning renal transplants and 76 receiving chronic haemodialysis were tested for HEV RNA and anti‐HEV IgG and IgM. Six hundred seventy controls were tested for anti‐HEV IgG. Anti‐HEV IgG was positive in 28/76 (36.8%) of haemodialysis and 16/88 (18.2%) of transplant patients. HEV RNA was not found in any patient. 126/670 (18.8%) of control subjects were anti‐HEV IgG positive. After adjusting for age and sex, there was a significantly higher anti‐HEV IgG seroprevalence amongst haemodialysis patients compared to controls (OR = 1.97, 95% CI = 1.16–3.31, P = 0.01) or transplant recipients (OR = 2.63, 95% CI = 1.18–6.07, P = 0.02). Patients with a functioning transplant showed no difference in anti‐HEV IgG seroprevalence compared to controls. The duration of haemodialysis or receipt of blood products were not significant risk factors for HEV IgG positivity. Patients receiving haemodialysis have a higher seroprevalence of anti‐HEV IgG than both age‐ and sex‐matched controls and a cohort of renal transplant patients. None of the haemodialysis patients had evidence of chronic infection. The reason haemodialysis patients have a high seroprevalence remains uncertain and merits further study. J. Med. Virol. 85:266–271, 2013. © 2012 Wiley Periodicals, Inc.